Tecnologia de gestão e práticas de treinamento: um estudo da tecnologia empresarial Odebrecht (TEO) na Braskem - Cruz, Arlete Lima da (2005)
The new work relations caused by constant changes in organizational environment bring in its structure, technological development and the creation of modern technologies which are related to products elaboration, services and people s management. In this context, the importance given to areas of training and development (T&D) is related to the model of the management. The aim of this research is to evaluate the impacts produced by a new technology of management, which is the Tecnologia Empresarial Odebrecht (TEO), applied on the training practices of a petrochemical company called Copene, which had its model of total management of productivity (TPM) modify and became a new company called Braskem, since its acquisition by the Odebrecht Group. To identify whether practices in human resources area (RH) and specially its subsystem of T&D had modification in its structure in order to attend the new technology demands, we were led to elaborate new research issues from three presumptions related to training practices: a) objectives which contain issues related to management model in use, human resources practices, structure and training purpose of the old model; b) implantation, asking about practices of updated training after the dissemination of the actual management model and c) assessment, aiming to identify the impact cause by the addition of the new technology. The study case method, using interviews and direct observation by the researcher, has conducted to an analysis of the impacts related specially by training focused on the individuals and organization needs. Modifications have occurred having as principal elements in the dissemination of the new technology process, employees of the administrative area. To the other integrant remain to accept the new way of management, whether being transmitted via formal training practices or in day-by-day activities such as, leadership. Relevant impacts were perceived on the Human Resources area and T&D on the acquired company, which started having as a principal focus the people, whilst the previous company was focus on business. When related to integrants, the more perceived modifications were referred to autonomy and responsibility that each employee acquires during the self-development and an understood as positive. We considered that the implantation of a new management technology requires an effective participation of all integrants of the organization independently of the actuation area and position they occupy. Subsystem of T&D can be an important vehicle to the integration and dissemination of that process.